Strategi Guru Terhadap Minat Baca Al-Qur’an pada Murid Kelas V di Sekolah Dasar Yayasan IBA Palembang - Rema Aulia; Tutut Handayani; Agra Dwi Saputra; Nurlaeli; Amir Hamzah (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2026)
Teachers' strategies have an important role in fostering interest in reading the Qur'an in elementary school students. However, in reality, some students still have less than optimal interest in reading the Quran, necessitating appropriate strategies from teacher. This study aims to analyze teachers' strategies for reading the Qur'an in students at SD Yayasan IBA Palembang and the factors that influence it. This research uses a qualitative approach with a case study type. The subjects of the study include PAI teachers, class V students, and school principals. Data was collected through observation, interviews, and documentation. Data analysis goes through the stages of data reduction, data presentation, and conclusion drawn, while the validity of the data is tested using triangulation of sources and techniques. The results of the study show that teachers' strategies include varied learning strategies, the use of learning media, and the implementation of learning evaluations. Supporting factors include student awareness, parental support, and school support, while inhibiting factors include limited learning time and less than optimal parental roles. Based on the results of the study, it can be concluded that teacher strategies that are varied, consistent, and supported by the school environment and family are able to increase interest in reading the Qur'an in elementary school students. This research is expected to be a reference for teachers and schools in developing interest in reading the Qur'an in students.